(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Aims: Finding descriptive data about facial index in Syrian males and females, and comparing it with other populations, and investigating the existence of a relationship between facial index and gender. Materials and methods: A descriptive-analytical study based on anthropometric measurements taken from the frontal photographs of the face at rest position. And the measurements were also taken using the traditional method (directly from the face using manual measuring tools) in order to compare them with measurements taken from the photographs to ensure the accuracy of the measurements. The measurements were also taken twice on the computer, at an interval of 10 days, and a third time by another qualified person, and the different results were compared statistically to ensure the accuracy of the measurement. The sample consists of 100 participants (50 males, 50 females) from the faculty of dentistry - Tishreen university. Results: The facial index differs according to different populations. The length, width, and facial index of the face are related to gender. The use of frontal photographs to measure the dimensions of the face is an accurate method compared to the traditional measurements with manual measuring tools.